Multi-agent architecture for a team of small robots (Publicaciones en Ciencias y Tecnología, 2007)
Using the distributed artificial intelligence and the distribuited robotics as a frame of reference, particularly the RoboCup World Championship, in this work and architecture for multiple mobile, autonomous, rational and coordinated agents is proposed. This architecture is composed of a mechanism of reasoning or automatic decision making, a functional and control structure, an artificial vision system, a navigation system, and a robotic architecture for a team of small minibots with capacity of acting at the Small Size League. In the design, development and construction of the components are coupled methods and techniques of Emergent Computation with models based on the traditional knowledge representation of Artificial Intelligence, producing algorithms that combine properties as adaptibility, robustness, uniformity with representation, inference and universality. The Agents are conformed by mechanisms that integrate sensors out of the body of the robot with effectors embedded in the robot and processes behaviors which are exhibited by the minibots while they operate in real time. The execution and performance of the architecture proposed had been experimented and evaluated through the implementation of a Multiagent System thar allows the operation of one or more robots on a testbed conformed by a football field made to comply with RoboCup rules.
Keywords: Multiagent System; Distributed Robotics; RoboCup